2015
DOI: 10.1007/s10854-015-3414-4
|View full text |Cite
|
Sign up to set email alerts
|

Microwave dielectric properties of CaV2O6 ceramics with low dielectric loss

Abstract: Novel glass-free low temperature firing microwave dielectric ceramics CaV 2 O 6 with high Q was prepared through a conventional solid-state reaction method. The crystal phase and microstructures were studied by XRD and SEM. Orientation degree of CaV 2 O 6 ceramics increased with an increase of sintering temperature. The Qxf values of CaV 2 O 6 ceramics were strongly correlated with the densification and orientation degree. Typically, the CaV 2 O 6 ceramics sintered at 675°C possessed excellent microwave dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For these high frequency wireless communication applications, the microwave dielectric materials should have a high dielectric constant, a high quality factor, and a near-zero temperature coefficient of resonant frequency, which are desirable for minimization of the microwave circuit component, maximum signal intensity and adaptation to environmental temperature changes [5,6]. At present, many compounds were reported for the possible use in microwave applications [7][8][9][10]. Among of several kinds of dielectric ceramics, wolframite-type CoZrNb 2 O 8 ceramics possess a high quality factor combined with appropriate dielectric constant, which are suitable candidate materials for contemporary miniaturized and integrated passive components application [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For these high frequency wireless communication applications, the microwave dielectric materials should have a high dielectric constant, a high quality factor, and a near-zero temperature coefficient of resonant frequency, which are desirable for minimization of the microwave circuit component, maximum signal intensity and adaptation to environmental temperature changes [5,6]. At present, many compounds were reported for the possible use in microwave applications [7][8][9][10]. Among of several kinds of dielectric ceramics, wolframite-type CoZrNb 2 O 8 ceramics possess a high quality factor combined with appropriate dielectric constant, which are suitable candidate materials for contemporary miniaturized and integrated passive components application [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this decline in quality factor could be due to the inhomogeneous microstructure and abnormal grain growth confirmed by SEM analysis . It should be noted that the difference between the Q × f values of the CaV 2 O 6 samples in the present study in comparison with that obtained by Yao et al would be due to the different conditions of fabrication process such as purity and grain size of the raw materials as well as the measurement conditions.…”
Section: Resultsmentioning
confidence: 37%
“…12,13 Therefore, finding ceramics with intrinsically low sintering temperature as well as appropriate microwave dielectric properties is the main aim of the recent studies. In recent years, there have been a number of different studies through which several vanadate compounds, such as Ca 5 A 4 (VO 4 ) 6 (A 2+ =Mg, Zn), 14 21 synthesized this ceramic using a solid-state reaction method and reported that the sample sintered at 675°C represented microwave dielectric properties of ε r = 10.2, a high-quality factor (Q × f) of 123 000 GHz (at 10.2 GHz) and a negative τ f of −63 ppm/°C, but chemical compatibility of this ceramic with electrode materials has not been investigated. According to another report about one of the other vanadium based ceramics, the BaV 2 O 6 ceramic sintered at 550°C exhibited microwave dielectric properties of ε r = 11.2, Q × f=42 790 GHz, and τ f =28.2 ppm/°C (a positive τ f compared with CaV 2 O 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in recent years, several new low-fired ceramics, such as vanadates like Ca 5 Zn 4 (VO 4 ) 6 , Mg 3 (VO 4 ) 2 and Sr 2 V 2 O 7 have been studied [19]. Among them, the CaV 2 O 6 ceramics prepared at 670 °C by Yao et al [20] presented superior performance of ε r ≈ 10, Q×f ≈ 123,000 GHz and τ f ≈ −63 ppm/°C.…”
Section: Previous Researches Have Revealed That Znomentioning
confidence: 99%